2004
DOI: 10.1159/000080972
|View full text |Cite
|
Sign up to set email alerts
|

A 12-Month Study of the Efficacy of Rivastigmine in Patients with Advanced Moderate Alzheimer’s Disease

Abstract: The efficacy of a centrally active cholinesterase inhibitor, rivastigmine tartrate (ENA 713), in patients with advanced moderate Alzheimer’s disease (AD) was evaluated in a 12-month placebo-controlled study. We aimed to investigate whether there was any evidence for the benefits of rivastigmine in patients with severe disease. These patients were compared with matched controls. In this study, 24 patients with advanced moderate AD received rivastigmine for 12 months. Another 20 patients received placebo. Mean d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 67 publications
1
28
0
1
Order By: Relevance
“…Twenty‐six of these 57 RCTs (46%) discussed clinical significance (Supporting Information, Table S1—for on‐line viewing only at http://www.interscience.wiley.com). 18–43 All 26 trials were rated as high quality, with a Jadad/Schultz score of 4 or greater.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐six of these 57 RCTs (46%) discussed clinical significance (Supporting Information, Table S1—for on‐line viewing only at http://www.interscience.wiley.com). 18–43 All 26 trials were rated as high quality, with a Jadad/Schultz score of 4 or greater.…”
Section: Resultsmentioning
confidence: 99%
“…Most of these treatments are mainly pharmacological. Several studies have shown an improvement in cognitive functions with this type of treatments for short periods [5,6] as well as periods longer than a year [7] . Besides, in later studies an improvement in patients' ability to perform daily activities has also been reported [8] .…”
Section: Introductionmentioning
confidence: 96%
“…Overall (I 2 = 99.1%, p = 0.000) Note: Weights are from random effects analysis Study ID WMD (95% CI) Weight % Karaman (2005) [26] Winblad et al (2007a) [16] Winblad et al (2007b) [16] Winblad et al (2007c) [16] Grossberg et al (2011a) [24] Grossberg et al (2011b) [24] Grossberg et al (2011c) [24] Grossberg et al (2011d) [24] Grossberg et al (2011e) [ between studies was tested using I 2 index and the equation is…”
Section: Methodsmentioning
confidence: 99%